Psychophysiological Determinants of Repeated Ventilator Weaning Failure: An Explanatory Model - Chen, Y.-J.; Jacobs, W. J.; Quan, S. F.; Figueredo, A. J.; Davis, A. H. T. (American journal of critical care, 2011)
The adverse effects of a failed ventilator weaning trial on the subsequent weaning attempts are not well understood. To examine physiological and psychological factors that may be predictive of risk for repeated weaning failures and prolonged mechanical ventilation. A prospective predictive study of 102 subjects, age 34 to 91 years, whose first ventilator weaning trial was unsuccessful but who were physiologically ready for another weaning attempt. Subjects were recruited from intensive care units and a respiratory care center of a tertiary medical center. Validated self-report scales and a Bicore monitoring system were used to measure ventilator patients' psychophysiological performance during the second weaning trial. Structural equation modeling was used to analyze the data and test the model. Significant causal pathways were found between fear and anxiety (r = 0.77; P < .001), anxiety and respiratory function (r = 0.24; P < .05), and respiratory function and weaning outcomes (r = 0.42; P < .001). The overall model predicted that both physiological and psychological factors were important in determining repeated failure of ventilator weaning, and the data were in support of the model (χ(2) = 29.49, P > .05). Patients whose first ventilator weaning trial is unsuccessful may be markedly fearful. Left unaddressed, these fears cause high anxiety levels that significantly compromise respiratory function and contribute to subsequent weaning failures. Thus begins a vicious cycle of repeated failure of ventilator weaning and prolonged mechanical ventilation.